Marriage is Scary Among Indonesian Youth: Theological and Social Perspectives - Ghazali, Muhammad; Rahmadani, Rahmadani; Pranajaya, Syatria Adymas; Suardi, Suardi; Alfiyanto, Afif; Ridho, Miftahur (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
The phenomenon of